V.PhyloMaker2: An updated and enlarged R package that can generate very large phylogenies for vascular plants - Yi Jin; Hong Qian (Plant Diversity, 2022)
An earlier version of V.PhyloMaker has been broadly used to generate phylogenetic trees of vascular plants for botanical, biogeographical and ecological studies. Here, we update and enlarge this package, which is now called ‘V.PhyloMaker2’. With V.PhyloMaker2, one can generate a phylogenetic tree for vascular plants based on one of three different botanical nomenclature systems. V.PhyloMaker2 can generate phylogenies for very large species lists (the largest species list that we tested included 365,198 species). V.PhyloMaker2 generates phylogenies at a fast speed. We provide an example (including a sample species list and an R script to run it) in this paper to show how to use V.PhyloMaker2 to generate phylogenetic trees.